Dinosaurs - Grace Maccarone (New York Scholastic Inc., 2001)
An exciting easy reader takes youngsters on a journey to the time of the dinosaurs by providing a wealth of fascinating facts, vibrant illustrations, and an appendix of all the dinosaurs listed in the book. Original.
Keywords: Level Reader -- Level Reader